1999
DOI: 10.1002/(sici)1522-2675(19990707)82:7<981::aid-hlca981>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Phase-Transfer Catalysis by Quaternary Ammonium Ions Derived fromCinchona-Alkaloid Analogs Containing 1,1′-Binaphthalene Moieties

Abstract: The synthesis and catalytic properties of a new type of enantioselective phase‐transfer catalysts, incorporating both the quinuclidinemethanol fragment of Cinchona alkaloids and a 1,1′‐binaphthalene moiety, are described. Catalyst (+)‐(aS,3R,4S,8R,9S)‐4 with the quinuclidine fragment attached to C(7′) in the major groove of the 1,1′‐binaphthalene residue was predicted by computer modeling to be an efficient enantioselective catalyst for the unsymmetric alkylation of 6,7‐dichloro‐5‐methoxy‐2‐phenylindanone (1; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…In alkylation reactions O ‐allyl‐ N‐ anthracenylmethyl (third‐generation) catalysts are usually the most efficient cinchona‐alkaloid catalysts 199. 200 These molecules can be prepared either by multistep synthesis or, more conveniently, in situ 201. The one‐pot procedure is particularly suitable for automated catalyst screening.…”
Section: Enantioselective Phase‐transfer Reactions195mentioning
confidence: 99%
“…In alkylation reactions O ‐allyl‐ N‐ anthracenylmethyl (third‐generation) catalysts are usually the most efficient cinchona‐alkaloid catalysts 199. 200 These molecules can be prepared either by multistep synthesis or, more conveniently, in situ 201. The one‐pot procedure is particularly suitable for automated catalyst screening.…”
Section: Enantioselective Phase‐transfer Reactions195mentioning
confidence: 99%
“…The ability of these compounds to function as phase‐transfer catalysts in the asymmetric allylation of 9 a under similar conditions were evaluated. These studies revealed that, without any optimization, 12 a was superior to the other three diastereomeric catalysts 12 b – d , although both the chemical yield and enantiomeric excess of 10 c were unsatisfactory (Scheme ) 8…”
Section: Alkylationmentioning
confidence: 99%
“…Die Eignung dieser Verbindungen als Phasentransferkatalysatoren wurde anhand der asymmetrischen Allylierung von 9 a unter ähnlichen Bedingungen untersucht. Ohne weitere Optimierungen war 12 a zwar den drei Diastereomeren 12 b – d überlegen, Ausbeute wie Enantiomerenüberschuss von Produkt 10 c waren aber unzureichend (Schema ) 8…”
Section: Alkylierungenunclassified